PLAYFUL PURSED-LIP BREATHING: PINWHEEL AND BUBBLE TECHNIQUES ON PULSE RATE, RESPIRATION, AND OXYGEN SATURATION IN TODDLER BRONCHOPNEUMONIA: A CASE REPORT - Triya Yestika Saleha; Novi Enis Rosuliana; Lia Herliana; Lusiana Dewi Savitri (Universitas Airlangga, 2026)
Introduction: Bronchopneumonia is a lower respiratory tract infection affecting the bronchioles and alveoli, causing inflammation, increased heart rate, shortness of breath, and decreased oxygen saturation. Pursed-Lip Breathing (PLB) can help improve breathing efficiency and increase oxygen levels. Purpose: To describe nursing care and the effects of modified PLB techniques (pinwheel and bubbles) on pulse rate, respiratory rate, and oxygen saturation in toddlers with bronchopneumonia. Methods: The study used a case report design in the form of participatory observation. Sampling was carried out using purposive sampling based on the diagnosis of bronchopneumonia with respiratory disorders, involving only two patients, in accordance with the characteristics of case reports that focus on comparing specific cases. Results: There were observable changes after the intervention in pulse rate, respiratory rate, and oxygen saturation. First, the average decrease in pulse rate in patient 1 was 12.67 beats/minute, while in patient 2 it was 9.33 beats/minute, resulting in a difference of 3.34 beats/minute. Second, the average decrease in respiratory rate in patient 1 was 5.67 breaths/minute, while in patient 2 it was 3.33 breaths/minute, resulting in a difference of 2.34 breaths/minute. Third, the average increase in oxygen saturation in patient 1 was 3.33%, while in patient 2 it was 1.33%, resulting in a difference of 2%. During the PLB intervention, the patients appeared calmer, showed reduced restlessness, and demonstrated more cooperative responses. Conclusions: There were changes in pulse rate, respiratory rate, and oxygen saturation after PLB was applied in toddler patients. PLB is recommended as a nonpharmacological method to improve breathing, reduce dyspnea, and increase comfort in children.